Severini and the internationalization of Valori Plastici: Collaborations and correspondence between 1919 and 1922 - Mañero Cerutti, Sofía (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Among all the fascicles of the Valori Plastici magazine, its issue II-III stands out. While the magazine has always been characterized by a focus on Italy, this issue focuses on French Cubist art. It is proposed here as an objective to defend, through a documentary methodology that provides the unpublished documents consulted in the Archive of 900’(MART), that it was precisely Severini who was in charge of making that issue and that with it he established a short period of relations between the artists linked to the Valori Plastici and himself, with interesting consequences for communication between the Italian and French artistic fields.